(untitled) (Development Service Industry Management, 2025)
The modern tourism market is characterized by high dynamics, digitalization, and growing consumer expectations, which necessitate the use of cutting-edge information technologies in the promotion of tourism products. In Ukraine, an increasing number of tourism companies are turning to digital communication channels, online booking systems, CRM platforms, and social media marketing (SMM) to enhance the effectiveness of their marketing activities. However, the level of IT adoption remains uneven, especially among small and medium-sized enterprises. Information technologies enable the personalization of offers, optimization of customer interactions, and increased competitiveness in both domestic and international markets. The aim of this study is to justify the effectiveness of using omnichannel marketing as a modern tool for the innovative promotion of tourism and hospitality products and services, as well as to develop recommendations for its implementation under the conditions of digital market transformation. In the highly competitive tourism services market, omnichannel marketing allows for the creation of a seamless communication flow with potential clients, which contributes to the effective promotion of tourism products. Omnichannel marketing is a strategy that integrates all communication channels and customer touchpoints, creating a unified, integrated platform for promoting products and services. A key feature of omnichannel marketing is that it is not limited to a single channel (e.g., websites or social media), but rather encompasses all possible avenues of interaction with the audience—from online platforms to offline interfaces. This integrated promotion of tourism products through omnichannel marketing enhances reach and impact. The use of omnichannel marketing tools in the tourism business enables significant results in the promotion of products and services. Engaging various communication channels and ensuring uninterrupted interaction with customers through both online and offline touchpoints increases the effectiveness of marketing campaigns, boosts customer loyalty, and optimizes costs. For travel agencies, omnichannel marketing is a vital tool in a competitive environment and allows them to achieve strong performance in the market.